SISTEM INFORMASI PENJUALAN PADA DEPOT KAYU SERASAN JAYA 3 DENGAN METODE PENGEMBANGAN EXTREME PROGRAMMING - Areyanda Listianto; Suhartini; Fajriyah (Elkom : Jurnal Elektronika dan Komputer, 2023)
Serasan Jaya 3 Building Materials Wood Depot is a business engaged in the sale of building material products, especially wood. Until now the Serasan Jaya 3 Building Materials Timber Depot only uses a manual sales and transaction system, which in this case requires a new breakthrough to keep up with technological developments that are developing in the current era because basically almost all ages demand something practical and easier. By looking at some of the existing problems, the researcher tries to design and build an information system for selling goods at the Serasan Jaya 3 Building Materials Wood Depot based on Android, therefore, the author chose this topic for a thesis entitled "Android-Based Sales Information System at Wood Materials Depot Serasan Jaya 3 Building With the Extreme Programming Development Method” which of course provides speed and convenience for the public to make transactions using mobile phones or mobile-based communication devices such as smartphones, tablets, gadgets, and so on. So that it can make it easy for the Serasan Jaya 3 Building Materials Timber Depot to promote products, product prices and make it easier for people to buy products and find out the prices of building material products from mobile devices. Android-Based Sales Information System at the Serasan Jaya 3 Building Materials Wood Depot was built using UML (Unifield Modeling Language) as its design mode and Extreme Programming as a system development method..